2013
DOI: 10.1111/acer.12158
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Lifetime Alcohol Dependence: Results from the National Epidemiologic Survey on Alcohol and Related Conditions

Abstract: Background An extensive clinical literature has noted gender differences in the etiology and clinical characteristics of individuals with alcohol dependence (AD). Despite this knowledge, many important questions remain. Methods Using the 2001 to 2002 National Epidemiologic Survey on Alcohol and Related Conditions (n = 43,093), we examined differences in sociodemographic characteristics, psychiatric and medical comorbidities, clinical correlates, risk factors, and treatment-utilization patterns of men (N = 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
68
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 46 publications
(66 reference statements)
9
68
1
3
Order By: Relevance
“…For clarity, the plot shows only a random 10% of the data at each age. Consistent with previous research, this figure illustrates the sex difference in drinking behaviors (Khan et al, 2013), as well as the peak in drinking during the early 20s (Schulenberg et al, 1996). A visual inspection of the scatter plot of parental drinking index scores versus offspring scores indicates a linear relationship.…”
Section: Descriptive Resultssupporting
confidence: 87%
“…For clarity, the plot shows only a random 10% of the data at each age. Consistent with previous research, this figure illustrates the sex difference in drinking behaviors (Khan et al, 2013), as well as the peak in drinking during the early 20s (Schulenberg et al, 1996). A visual inspection of the scatter plot of parental drinking index scores versus offspring scores indicates a linear relationship.…”
Section: Descriptive Resultssupporting
confidence: 87%
“…Surprisingly few papers focused on young adults [226,227]; those that did also found comorbidity. Regardless of the focal disorder or symptom of the paper, studies addressing gender generally found greater internalizing comorbidity in women and externalizing comorbidity in men [57,61,67,68,228-230]. …”
Section: Major Findingsmentioning
confidence: 99%
“…1 Historically, the prevalence of alcohol use and related harms has been between 2 and 12 times higher in men than women. [2][3][4][5][6][7] However, there is emerging evidence to suggest that the gap between men and women in alcohol use and related harms is closing among recently born cohorts. [8][9][10][11] Understanding sex-specific birth cohort trends in the epidemiology of alcohol use is vital as they point to key environmental and social mechanisms associated with population shifts in alcohol use patterns.…”
mentioning
confidence: 99%